Studi Evaluatif Berbasis Model Diskrepansi Terhadap Implementasi Asesmen Autentik Pada Mata Pelajaran Pendidikan Agama Kristen Kelas Viii Di SMP Kristen Kota Kupang - Anita Ege Udju (Institut Agama Kristen negeri Kupang, 2022)
This study aims to determine and describe the discrepancy that occurs between ideal conditions and real conditions related to the implementation of authentic assessments in Christian Religious Education subjects according to the 2013 curriculum. that the assessment carried out only focuses on results without looking at the process. The method used in this research is descriptive quantitative. The results of this study are; (1) Discrepancies at the assessment planning stage are quite wide; product assessment is classified as small; portfolio assessment is small; project assessment is small, performance assessment is small. (2) The discrepancy at the self-assessment implementation stage is quite wide; small portfolio assessment; project assessment is small; performance assessment is quite broad. (3) Discrepancy at the self-assessment reporting stage is very wide, product assessment is small, portfolio assessment is small, project assessment is small, performance assessment is quite wide. The most dominant factor causing discrepancies is the lack of training related to the implementation of authentic assessments for Christian religious education teachers.